Microscopic analysis of the evolution of asphalt colloidal properties and rejuvenation behavior in aged asphalt. (10th March 2022) - Bao, Chonghao; Zheng, Chuanfeng; Xu, Yan; Nie, Lei; Luo, Haisong
Abstract: The performance restoration of aged asphalt is a challenge in the current technology available for pavement rejuvenation. Investigating the evolution of aged asphalt colloids from a microscopic perspective is the key to solving this problem. In this study, asphalt colloids and aggregates were modeled according to molecular simulation. The thermodynamic properties of colloids were investigated by viscosity and cohesive energy density (CED). The microstructural evolution and energy in colloids were examined using radial distribution function (RDF), binding energy, electrostatic potential (ESP), and interaction potential curve after annealing simulations. Rejuvenators were introduced into the aged asphalt colloid and aggregate models to investigate asphalt rejuvenation behavior. The thermodynamic and colloidal microstructural changes caused by these configurations were further verified. The results showed a significant increase in viscosity and CED of aged asphalt colloids. The results of RDF and quantum mechanical calculations indicate that oxidative aging enhances the strength and density of asphaltene aggregates and also contributes to forming stable rejuvenated configurations. Under the influence of rejuvenators, asphaltene aggregates can form four rejuvenated configurations: "block, " "sandwich, " "T-shape, " and "occupy." The sandwich and occupy configurations are characterized by the stacking effect of aromatic rejuvenators. The block configuration is caused by the steric hindrance effect of long-chain rejuvenators. The T-shape configuration is common in both effects. The polarity of rejuvenators improves electrostatic interactions and contributes to rejuvenation configurations, but also leads to extra hydrogen bonds and enhanced aggregation. The rejuvenation of aggregates can be considered the formation of new stable configurations under thermal motion. Recovery results of aged asphalt indicate that effective rejuvenation can be achieved using low-polarity aromatic rejuvenators and high-polarity long-chain rejuvenators. Highlights: Oxidation increases the intensity and diversity of asphaltene dimer configurations. Rejuvenator prevents the formation of the lowest energy configuration of the dimer. "Block, " "sandwich, " "T-shape" and "occupy" are major rejuvenated configurations. Balanced size and polarity of rejuvenator are the keys to microstructure recovery.